Dual heterogeneous Cu–Al2O3/Cu laminated composite with high strength and ductility prepared by accumulative roll bonding - Renpeng Chen; Weijie Qian; Haiyan Liu; Weibin Xie; Huiming Chen; Hang Wang; Bin Yang (Journal of Materials Research and Technology, 2024)
Cu–Al2O3/Cu laminated dual heterogeneous microstructure composites with alternating coarse/fine grain distributions were prepared using a combination of accumulative roll bonding and annealing processes. The average layer thickness of the Al2O3/Cu layers is 2.1 μm and that of the Cu layer is 4.2 μm, and meanwhile, the average grain size of the Al2O3/Cu layers and Cu layers are 0.25 μm, 2.3 μm respectively. The strength of Al2O3/Cu layer is higher than that of the Cu layer because of the additional dispersion strengthening and the stronger grain boundary strengthening. Owing to significant differences in the structural and mechanical properties of the layers in this material, geometrically necessary dislocations accumulated at the interface during the tensile process; this resulted in significant heterogeneous deformation-induced strengthening, which yielded a laminated composite with a tensile strength of 413 MPa, tensile ductility of 27%, and excellent overall performance. This work provides a new design strategy for the preparation of high-strength high-ductility materials.